2010
DOI: 10.2298/vsp1008617g
|View full text |Cite
|
Sign up to set email alerts
|

Maternal autoimmune thyroid disease and pregnancy complication

Abstract: Controlling thyroid diseases reduces pregnancy complications. Development of gestational diabetes in hypothyroid patients requires controlling glycoregulation in all pregnant women with hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
2
5
1
2
Order By: Relevance
“…In the study by Sharmeen et al there was a positive association which was similar to another study by Nazarpour et al in Iran. 5,8 Increased association was also found in the study by Mannisto et al between hypothyroidism in pregnancy and preeclampsia as well by Goel et al 2,3 No association with hypertensive disorders were found by Medici et al as well as by Kumru et al 7,9 Similar results were reported in the study by Gudovic et al 6 In this study there was no increased association for the development of hypertension in the case and control groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the study by Sharmeen et al there was a positive association which was similar to another study by Nazarpour et al in Iran. 5,8 Increased association was also found in the study by Mannisto et al between hypothyroidism in pregnancy and preeclampsia as well by Goel et al 2,3 No association with hypertensive disorders were found by Medici et al as well as by Kumru et al 7,9 Similar results were reported in the study by Gudovic et al 6 In this study there was no increased association for the development of hypertension in the case and control groups.…”
Section: Discussionsupporting
confidence: 87%
“…5 In another study by Mannisto et al it was observed that hypothyroid pregnant women have increased odds for developing this complication. 2 Hypothyroidism in pregnancy was more frequently associated with gestational diabetes in a study by Gudovic et al whereas no association was found in another study conducted in Turkey by Kumru et al 6,7 In the present study there was a statistically significant number of gestational diabetes in the case group compared to controls (p=0.00001).…”
Section: Discussioncontrasting
confidence: 57%
“…4 In a study by Mannisto et al it was observed that hypothyroid pregnant women have increased odds for developing GDM. 8 Similar results were found in their study by Gudovic et al 9 However, no comparison is available on the occurrence of this medical disorder in GDM pregnancies treated by diet therapy alone and those requiring insulin. In our present study no, significant difference was observed between the two GDM groups regarding development of this complication.…”
Section: Discussionsupporting
confidence: 72%
“…Of these, most were excluded after the first screening based on abstract and/or title, and 17 citations were retained. Six studies [18][19][20][21][22][23] were excluded after fulltext review of the 17 articles. Finally, 11 cohort studies [24][25][26][27][28][29][30][31][32][33][34] including 56 055 pregnant women, of whom 3903 had SCH, were included in the analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%